Stored energy of plastic deformation in tube bending processes - Śloderbach, Zdzisław; Pająk, Janusz (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents an aproximate analytic method for determination of the stored energy of plastic deformation during cold bending of metal tubes at bending machines. Calculations were performed for outer points of the tube layers subjected to tension and compression (the points of maximum strains). The percentage of stored energy related to the plastic strain work was determined and the results were presented in graphs. The influence and importance of the stored energy of plastic deformation on the service life of pipeline bends are discussed.
Keywords: plastic deformation; tube bending; stored energy; austenitic steel; boiler steel